Human Development in South Asia 2005 : Human Security in South Asia. - Oxford University Press (New York Oxford University Press, 2006)
The Human Development Report in South Asia argues that to sustain economic growth South Asia needs to seriously address the human security concerns of the people. The wealth of data collected for the Report on South Asia's insecurity will be valuable for policymakers and academic researchers.
Published for The Mahbub ul Haq Human Development Centre
Keywords: South Asia -- Social conditions -- Economic history